The Effect of Operational Risk, Credit Risk And Revenue Diversification on Profitability - Muhammad Pondrinal; Ronni Andri Wijaya; Berta Agus Petra; Thariq Al Adli (UPI YPTK Journal of Business and Economics, 2022)
This study aims to determine the effect of Operational Risk, Credit Risk and Income Diversification on Profitability in banking companies listed on the IDX for the 2016-2020 period.The analytical method used is Panel Data Regression analysis. The results obtained from this study: i) Operational Risk has a positive and significant effect on profitability in banking companies listed on the IDX for the 2016-2020 period. ii) Credit Risk has a negative and significant effect on profitability in banking companies listed on the IDX for the 2016-2020 period. iii) Income Diversification has a negative and significant effect on profitability in banking companies listed on the IDX for the 2016-2020 period. iv) Operational Risk, Credit Risk and Diversification have a positive and significant simultaneously positive and significant effect on Profitability in Banking companies listed on the IDX for the 2016-2020 period.